Interactive E-Learning Courses – As A New Teaching Method - Sodiqovich, Usmonov Murod; Burxonovich, Abdullayev Xolxuja; Mamarasulovich, Suvonqulov Baxtiyor (Indonesian Journal of Education Methods Development, 2018)
This article discusses the use of interactive training courses, their features, differences from ordinary training courses. The article also develops a model of a multimedia interactive e-learning course and discusses its advantages